Teacher factors as determinants of achievement in intergrated science (2003)
The study investigated how some teacher variables such as qualification, teaching experience in integrated science, area of specialization, gender teacher's knowlegde of the objectives of integrated science, teaching strategies employed and their assessment practices determine or predict achievement in integrated science. To do this, an eight variable model was constructed and tested in order to provide casual explanations of achievement in integrated science. Forty teachers and five hundred students randomly selected from twenty schools in Oyo state were involved in the study. Data collection was carried out using three instruments with reliability coefficient ranging from 0.72-0.08. Data analysis was carried out through the multiple regression analysis procedure and path analysis techniques. The results indicates that the seven predictor variables accounted for 17. 6% of the variation in the criterion variable. Out of this, having the knowledge of the objectives of the programme contributed most followed by the qualification of the teacher. The implications of all these for professional development is also discussed.